Focusing on cyclin-dependent kinases 5: A potential target for neurological disorders - Tian, Zhen; Feng, Bin; Wang, Xing-Qin; Tian, Jiao (Frontiers in Molecular Neuroscience, 2022)
Cyclin-dependent kinases 5 (Cdk5) is a special member of proline-directed serine threonine kinase family. Unlike other Cdks, Cdk5 is not directly involved in cell cycle regulation but plays important roles in nervous system functions. Under physiological conditions, the activity of Cdk5 is tightly controlled by p35 or p39, which are specific activators of Cdk5 and highly expressed in postmitotic neurons. However, they will be cleaved into the corresponding truncated forms namely p25 and p29 under pathological conditions, such as neurodegenerative diseases and neurotoxic insults. The binding to truncated co-activators results in aberrant Cdk5 activity and contributes to the initiation and progression of multiple neurological disorders through affecting the down-stream targets. Although Cdk5 kinase activity is mainly regulated through combining with co-activators, it is not the only way. Post-translational modifications of Cdk5 including phosphorylation, S-nitrosylation, sumoylation and acetylation can also affect its kinase activity and then participate in physiological and pathological processes of nervous system. In this review, we focus on the regulatory mechanisms of Cdk5 and its roles in a series of common neurological disorders such as neurodegenerative diseases, stroke, anxiety/depression, pathological pain and epilepsy.